The tip of the iceberg: a distinctive new spotted-wing Megaselia species (Diptera: Phoridae) from a tropical cloud forest survey and a new, streamlined method for Megaselia descriptions - Hartop, Emily A. (Biodivers Data J, 2014)
Abstract. A new Megaselia species, M. shadeae, with a large, central, pigmented and bubble-like wing spot and a greatly enlarged radial wing vein fork, is described from Zurquí de Moravia, Costa Rica. As part of the Zurquí All Diptera Biodiversity Inventory (ZADBI) project, it represents the first of an incredible number of new phorid species to be described from this one Costa Rican cloud forest site. A new, streamlined method of description for species of this enormous genus of phorid flies is presented.